Creating a career as a woman composer: Implications for music in higher education - Bennett, Dawn; Macarthur, S.; Hope, C.; Goh, T.; Hennekam, S. (Cambridge University Press, 2018)
Recent decades have seen gender and feminist research emerge as major fields of enquiry in musicology and to a far lesser extent, music education. While these fields have increased awareness of the issues confronting women and other marginalised groups, the pedagogical practices and curricular design that might support aspiring women composers are in urgent need of attention. This article reports from an international survey of women composers (n=225), who in western art music continue to experience a masculine bias that has its roots in the past. The findings in the survey were focused on income, work and learning, relationships and networks, and gender. Numerous composers surveyed noted the under-representation of music composed by women in their higher education curricula. They also described their unpreparedness for a career in music. The article explores the issue of gender in music composition and makes practical recommendations for a more gender balanced music curriculum in higher education.